Conocimiento y ansiedad del familiar del paciente en unidad de cuidados intensivos - Reyes Carranza, Nataly Marita (2019)
The present correlational and descriptive research was made with the purpose of determining the relationship between the level of knowledge and the degree of anxiety of the patient in critical situation in Intensive Care Unit of Belen Hospital of Trujillo between January and April 2016. We used two instruments validated to collect the information: one of these was about Knowledge Level and the other was about Hamilton's Anxiety Level, applying to the relatives of the patients in a time of 20 minutes and respecting the ethical principles. Chi- square statistic was used to correlate the variables, and we obtained the following conclusions: 73.33% of family members had a regular level of knowledge about the critical situation of their patient, 16.67% had good level and only 10% had deficient level. 73% of family members reported a moderate degree of anxiety compared to their critical situation, 14 percent had mild degree and 13% had severe degree. The test reflects that there is statistically significant relationship between the level of knowledge and degree of anxiety with P-value = 0.001.